How do you balance #HBr + Mg(OH)_2 -> MgBr_2 + H_2O#?

1 Answer
Apr 1, 2016

Answer:

i will tell u the steps.

Explanation:

Let the equation be

a #HBr# + b #Mg(OH)_2# #-># c #MgBr_2+d H_2O#

Equating #H#-atoms on both sides,

a+2b=2d

Equating #Br# on both sides,

a=2c

Equating #Mg# on both sides,

b=c

Equating #O# on both sides,

2b=d

So..........a+2b=2d
#rArr# 2c+2(c)=2d
#rArr# 4c=2d
#rArr# d=2c

Finally, substituting a,b,c,d

2c # HBr# + c #Mg(OH)_2# #-># c #MgBr_2# + 2c #H_2O#

2 # HBr# + #Mg(OH)_2# #-># #MgBr_2# + 2 #H_2O#